The Ben Franklin book of easy and incredible experiments - Rudy, Lisa Jo.; Noll, Cheryl Kirk; Franklin Institute (Philadelphia, Pa.). Science Museum (New York : Wiley, 1995)
Young scientists everywhere can explore and enjoy science Ben Franklin style.
The life of Benjamin Franklin, 1706-1790 -- Using your head -- Exploring the weather -- Exciting electricity -- Making music -- Paper and printing -- Exploring light and sound.
"A Franklin Institute Science Museum book."
Includes bibliographical references and index.
Keywords: Science -- Experiments; Science -- Experiments -- Juvenile literature; Engineering -- Experiments; Engineering -- Experiments -- Juvenile literature; Franklin, Benjamin, -- 1706-1790.; Science -- Experiments; Engineering -- Experiments; Experiments